2017
DOI: 10.3390/ijms18122572
|View full text |Cite
|
Sign up to set email alerts
|

Structural Masquerade of Plesiomonas shigelloides Strain CNCTC 78/89 O-Antigen—High-Resolution Magic Angle Spinning NMR Reveals the Modified d-galactan I of Klebsiella pneumoniae

Abstract: The high-resolution magic angle spinning nuclear magnetic resonance spectroscopy (HR-MAS NMR) analysis of Plesiomonas shigelloides 78/89 lipopolysaccharide directly on bacteria revealed the characteristic structural features of the O-acetylated polysaccharide in the NMR spectra. The O-antigen profiles were unique, yet the pattern of signals in the, spectra along with their 1H,13C chemical shift values, resembled these of d-galactan I of Klebsiella pneumoniae. The isolated O-specific polysaccharide (O-PS) of P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…The core OS of P. shigelloides 90/89 is similar to the previously reported core oligosaccharide of P. shigelloides strain CNCTC 78/89 [22], differing only by one sugar residue in the outer core, that is the 6-substituted Glc instead of the 6-substituted GlcN. In the core OS of P. shigelloides O33 [20], both glycoforms, containing 6-substituted GlcN or 6-substituted Glc and O-acetylation of the terminal GalNAc, were reported.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The core OS of P. shigelloides 90/89 is similar to the previously reported core oligosaccharide of P. shigelloides strain CNCTC 78/89 [22], differing only by one sugar residue in the outer core, that is the 6-substituted Glc instead of the 6-substituted GlcN. In the core OS of P. shigelloides O33 [20], both glycoforms, containing 6-substituted GlcN or 6-substituted Glc and O-acetylation of the terminal GalNAc, were reported.…”
Section: Discussionsupporting
confidence: 86%
“…Structural analysis indicated that the core OS ( Figure 1 a,d and Table 1 ) is similar to the previously identified core oligosaccharide of P. shigelloides strain CNCTC 78/89 [ 22 ]. Both structures were undecasaccharides and differed by only one sugar residue in the outer core region.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations